EC16 Nanoformulation: A Potential Nasal Drug for Treating Long COVID - Garrison Lovett; Stephen Hsu (Elsevier, 2024)
OBJECTIVES: To test the effectiveness of EGCG palmitate (EC16), a lipophilic derivative of (-)-epigallocatechin-3-gallate (EGCG, an anti-oxidant catechin component found in green tea), in reducing the neurological complications of persistent SARS CoV-2 infection particularly in the Human Olfactory Epithelium. The goal of this project was to evaluate the in vitro properties and antiviral activity of a prototype aqueous EC16 nanoformulation. METHODS: Nanoparticles of EC16 were obtained by a natural-forming method. Nanoparticle size and Zeta potential were measured by the ZetaView Nanoparticle Tracking Analysis (NTA) system. The pH and viscosity of the formulations were measured. Contact suspension antiviral activity of EC16 nanoformulations against OC43 β-coronavirus was determined by TCID50 assay in human respiratory fibroblast cells (MRC-5). Post-infection antiviral activity of the EC16 nanoformulation was assessed using human nasal primary epithelial cells (HNpECs). Cytotoxicity tests were conducted by MTT assay in HNpECs and HCT-8 cells. RESULTS: A nanoformulation containing 0.1% w/v EC16 inactivated 99.9999% of OC43 on direct contact within 1 minute. After a single 10-minute incubation of HNpECs with formulation EC16m (EGCG-4' monopalmitate) nanoformulation, OC43 viral replication was inhibited by 99%. Cytotoxicity tests showed that EC16 nanoformulations were comparable to normal saline commonly used in nasal irrigations.] CONCLUSIONS: The prototype of a nasal nanoformulation containing EC16 showed potential capabilities to rapidly inactivate SARS-CoV-2 virus in the olfactory epithelium. The results indicated that these novel nanoformulations could be the basis for a nasal drug for treatment of Long- COVID associated anosmia and other associated neurological symptoms, pending future clinical studies. IMPLICATION: EC16, a food-grade compound derive from natural materials, has the potential to be a novel intranasal drug for the treatment of Long COVID, pending safety studies and optimization of a specific nasal spray formulation. Additionally, future studies will determine the antiviral effectiveness of EC16 for pathogens besides SARS-CoV-2, such as norovirus, herpes simplex virus, and influenza viruses, etc...